2020
DOI: 10.1021/acs.est.9b07221
|View full text |Cite
|
Sign up to set email alerts
|

Novel Simultaneous Removal Technology of NO and SO2 Using a Semi-Dry Microwave Activation Persulfate System

Abstract: As it has a simple system and a small floor area, flue gas simultaneous desulfurization and denitrification technology has a good development prospect, and related research has become a hot topic in the field of flue gas purification. In this work, a novel simultaneous removal technology of NO and SO 2 from flue gas using a semi-dry microwave activation persulfate system was developed for the first time. A series of experiments and characterization analyses had been implemented to research the feasibility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 81 publications
1
39
0
Order By: Relevance
“…Relevant results ,,,, showed that compared with ultrasonic, photochemical and electrochemical activation, microwave activation had longer radiation distance because it can even penetrate solids, possessing a good prospect of application. In the field of water treatment, some researchers employed microwave to activate peroxides (i.e., H 2 O 2 , PS, and PMS) to generate free radicals to degrade organic contaminants from wastewater. ,,,,,,,, However, microwave-activated SO 4 • – -based AOTs are not suitable for wastewater treatment because most of the microwave radiation energy will be consumed in heating and evaporation of water, instead of activating oxidants.…”
Section: Progress In So4•–-based Aots For Gaseous Pollutant Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…Relevant results ,,,, showed that compared with ultrasonic, photochemical and electrochemical activation, microwave activation had longer radiation distance because it can even penetrate solids, possessing a good prospect of application. In the field of water treatment, some researchers employed microwave to activate peroxides (i.e., H 2 O 2 , PS, and PMS) to generate free radicals to degrade organic contaminants from wastewater. ,,,,,,,, However, microwave-activated SO 4 • – -based AOTs are not suitable for wastewater treatment because most of the microwave radiation energy will be consumed in heating and evaporation of water, instead of activating oxidants.…”
Section: Progress In So4•–-based Aots For Gaseous Pollutant Removalmentioning
confidence: 99%
“…In the field of gaseous pollutants removal, several researchers ,, used catalysts under microwave activation to remove gaseous pollutants. However, this kind of microwave activation system led to an operation temperature of over 1000 °C because of uncontrollable heating characteristics of microwave in a dry treatment device, which poses a great challenge to the life of catalysts and the safe of device operation. ,,,,,, …”
Section: Progress In So4•–-based Aots For Gaseous Pollutant Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…The global warming potential of N 2 O is 310 times higher than that of CO 2 [3], and soot is theoretically the second largest global warming factor after CO 2 due to its radiative forcing effect [1,4]. NO x also causes ozone layer destruction and acid rain [5]. In addition, NO x , CO, and VOCs cause human poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Dry simultaneous control technologies are promisingly investigated without large water assumptions and low secondary pollution. [15][16][17][18][19][20][21][22][23][24][25][26][27] Among the dry integrated multi-pollutant removal technologies, the carbon-based catalyst-integrated removal technology was widely studied, 28,29 particularly in the sintering ue gas industry. 30 Activated coke/activated carbon is used as a dry adsorbent.…”
Section: Introductionmentioning
confidence: 99%